KARAKTERISASI DAN JARAK KEMIRIPAN UWI (Dioscorea alata L.) BERDASARKAN PENANDA MORFOLOGI UMBI - Trimanto, Trimanto (Buletin Kebun Raya, 2012)
Yam (Dioscorea alata L.) is a potential local crop for supporting food security program in Indonesia.Â  Inventory and characterization of yam have been conducted in scattered population at Nganjuk region - East Java.Â  The research was aimed to identify the characteristic of Nganjukâs yam, based on the tuber morphology and to determine its similarity distance value.Â  The characterisation were analyzed using interval similarity function, based on NTSys DICE coefficient programme. The result showed that 22 accession numbers which comprises of 13 variants of yam were found in Nganjuk region. The same variants of yams indicated by their close similarity distance although they were originated from different areas.